Miracle near 34th street: Wartime Penicillin Research at St John's University, NY. Issue 4 (December 2017) - Shama, Gilbert
Highlights: Wartime penicillin research at St John's University, NY is examined. The association of penicillin with miraculous cures is seen as a motivating factor. Work undertaken by Sr. Immaculate shows links to the tenets of Catholicism. Abstract : In the spring of 1944 Sister Marie Immaculate was awarded a Master of Science degree for research on penicillin which she had conducted at St John's University in Brooklyn, New York. She gave her motivation for undertaking research in this topic as wishing to fulfil her patriotic duty by participating in the quest towards making penicillin more readily available to all who needed it. It is possible that contemporary media reports suggesting that the power of penicillin was comparable to a miracle cure contributed to her interest in the subject at the time. In practical terms, her work was to have no bearing in increasing the availability of penicillin, but simply by becoming engaged in this endeavour, it could be argued that she was enacting the beliefs underlying her religious calling. This article explores those beliefs, and proposes an ideological synergy between science and religion in respect to Sister Marie Immaculate's faith in penicillin's potential to cure the world's ills.